Comparative evaluation of nutritional composition, phytochemicals and sensorial attributes of lyophilized vs conventionally dried Grewia asiatica fruit pulp powder - Saima Latif; Muhammad Sohaib; Sanaullah Iqbal; Muhammad Hassan Mushtaq; Muhammad Tauseef Sultan (AIMS Agriculture and Food)
Grewia asiatica, commonly known as phalsa, is a widely cultivated fruit in Pakistan, valued for its nutritional and medicinal benefits. Being a perishable fruit with limited shelf life and rapid spoilage, a preservation approach is needed to extend fruit shelf life and product development. In this context, we aimed to extend the shelf life of G. asiatica fruit pulp using conventional and lyophilization drying and to evaluate their impact on nutritional composition, phytochemicals attributes, sensory evaluation and product shelf life for fruit pulp powder stored at ambient conditions for 3 months (0, 45th and 90th day). For the study, ripe G. asiatica fruit sourced from local farms were subjected to cleaning followed by drying using conventional and lyophilization processes. The resulting fruit powder was packed in sealed foil bags and stored at room temperature for 3 months, subjected to nutritional properties, phytochemicals, antioxidant capacity, and sensory evaluation on the 0, 45th, and 90th storage days. The results showed that both techniques increased the shelf life of powder. However, lyophilization resulted in better retention of vitamin C, antioxidant activity, and better free radical scavenging activity in fruit powder than conventional drying. Color parameters and sensory evaluation were also affected by drying and storage conditions as an advancement of storage resulted in decreased consumer acceptability. These findings demonstrate that lyophilization effectively preserves nutritional and phytochemical qualities of G. asiatica powder, making it a viable preservation approach for prolonging fruit shelf life while maintaining its health promoting compounds and functional properties. The lyophilized G. asiatica fruit pulp powder may have potential use in the food industry as an additive in ready-to-use products to enhance nutritional attributes, color, and better consumer acceptability for dried powders.